2011
DOI: 10.1158/1940-6207.capr-10-0369
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Dose–Response Study Using 3,3′-Diindolylmethane in the K14-HPV16 Transgenic Mouse Model: Cervical Histology

Abstract: The human papilloma virus is the major cause of cervical cancer. Viral infection initiates cervical intraepithelial neoplasia, which progresses through several stages to cervical cancer. The objective of this study is to identify the minimum effective dose of diindolylmethane that prevents the progression from cervical dysplasia to carcinoma in situ. We document cervical histology in K14-HPV16 mice receiving different doses of diindolylmethane. Urinary diindolylmethane concentrations are reported. Diindolylmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The K14-HPV16 mouse model is commonly used in studies involving cervical intraepithelial neoplasias and cancer, and provides the essential transition from in vitro to in vivo pre-clinical studies [31,32]. Topical application (locoregional) and dietary administration (systemic) of black raspberries and/or their bioactive components using the K14-HPV16 mouse model would assess the potential efficacy of black raspberries on the histopathology of progressive cervical lesions present in the transformation zone.…”
Section: Discussionmentioning
confidence: 99%
“…The K14-HPV16 mouse model is commonly used in studies involving cervical intraepithelial neoplasias and cancer, and provides the essential transition from in vitro to in vivo pre-clinical studies [31,32]. Topical application (locoregional) and dietary administration (systemic) of black raspberries and/or their bioactive components using the K14-HPV16 mouse model would assess the potential efficacy of black raspberries on the histopathology of progressive cervical lesions present in the transformation zone.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors revealed that DIM inhibits the development of E6/E7 oncogene-induced cervical lesions and increased serum INF-γ indicating increased immune response in the DIM-fed animals. Furthermore, to define the extent and the most effective minimum dose of DIM administration to augment the efficacy of preventive and therapeutic HPV vaccines, these investigators utilizing the K14-HPV16 transgenic mouse model concluded 1000ppm of DIM as the minimum effective and viable dose for future human studies [143]. The urinary DIM concentrations following 1000ppm DIM dose compare favorably to DIM measured in women taking either 200 or 400 mg of DIM twice daily for 4 weeks as reported earlier [138].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of DIM in K14-HPV16 transgenic mouse model of cervical cancer have also been evaluated and reported wherein 2,000 ppm DIM given for 12 weeks either delayed or inhibited the progression from cervical dysplasia to cervical cancer (Sepkovic et al 2009). To seek an answer for the most effective minimum dose of DIM administration for future human studies to augment the efficacy of preventive and therapeutic HPV vaccines, the dose of 1000 ppm of DIM was extrapolated as the minimum effective and viable dose for future human studies (Sepkovic et al 2011). This 1000 ppm DIM dose compare favorably to DIM measured in women taking either 200 or 400 mg of DIM twice daily for 4 weeks as reported earlier (Sepkovic et al 2001).…”
Section: Dim and Preclinical Studiesmentioning
confidence: 99%